Safety assessment of multiple systemic administration of human mesenchymal stem cell-conditioned medium for various chronic diseases - Norihito Inami (PLoS ONE, 2025)
Conditioned medium (CM) derived from human mesenchymal stem cells (MSCs) has shown potential as a therapeutic agent. However, the safety of its administration in human remains largely unexplored. This study evaluated the safety of multiple systemic administrations of MSC-CM, specifically adipose-derived and umbilical cord-derived MSC-CM, in 55 patients with various chronic diseases. Symptom assessments and blood tests were conducted before and after administration to monitor adverse events and measure the inflammatory marker C-reactive protein (CRP), respectively. The results demonstrated no serious adverse events attributed to MSC-CM administration. Although minor adverse events were observed, their causal relationship with MSC-CM remained unclear. Additionally, MSC-CM administration slightly reduced CRP levels, regardless of the administration route (intraarterial, intravenous, or inhalation). Additionally, a significant reduction in CRP levels was observed in patients with elevated CRP levels (CRP > 0.3) following MSC-CM administration. These findings suggest that repeated systemic administration of MSC-CM is likely safe and may have anti-inflammatory effects.